A rapidly deployed, interactive, online visualization system to support fatality management during the coronavirus disease 2019 (COVID-19) pandemic. (11th October 2020) - Kaul, Smiti; Coleman, Cameron; Gotz, David
Abstract: Objective: To create an online visualization to support fatality management in North Carolina. Materials and Methods: A web application aggregates online datasets for coronavirus disease 2019 (COVID-19) infection rates and morgue utilization. The data are visualized through an interactive, online dashboard. Results: The web application was shared with state and local public health officials across North Carolina. Users could adjust interactive maps and other statistical charts to view live reports of metrics at multiple aggregation levels (eg, county or region). The application also provides access to detailed tabular data for individual facilities. Discussion: Stakeholders found this tool helpful for providing situational awareness of capacity, hotspots, and utilization fluctuations. Timely reporting of facility and county data were key, and future work can help streamline the data collection process. There is potential to generalize the technology to other use cases. Conclusions: This dashboard facilitates fatality management by visualizing county and regional aggregate statistics in North Carolina.